2019
DOI: 10.14245/ns.1938192.096
|View full text |Cite
|
Sign up to set email alerts
|

Is Cervical Stabilization for All Cases of Chiari-I Malformation an Overkill? Evidence Speaks Louder Than Words!

Abstract: Chiari I malformation is characterized by the downward displacement of cerebellar tonsils through the foramen magnum. While discussing the treatment options for Chiari I malformation, the points of focus include: (1) Has the well-established procedure of posterior fossa decompression become outdated and has been replaced by posterior C1-2 stabilization in every case? (2) In case posterior stabilization is required, should a C1-2 stabilization, rather than an occipitocervical fusion, be the only procedure recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…However, previous studies clearly demonstrated clinical efficacy with decompression alone and probably remains a suitable treatment option for CM with no signs of instability [11,54]. In summary, we agree with Deora and colleagues that in patients with pure CM with symmetrical C1/2 joints and no signs of instability, PFD and duraplasty is an established, effective, and safe treatment option with excellent long-term outcome [18,28,62,89]. In patients with instability, C1-2 fusion with distraction or OCF with or without transoral decompression in selected cases are potential treatment options that have to be considered in this patient population.…”
Section: Chiari Malformation Type I-discussion Of Evidencesupporting
confidence: 79%
“…However, previous studies clearly demonstrated clinical efficacy with decompression alone and probably remains a suitable treatment option for CM with no signs of instability [11,54]. In summary, we agree with Deora and colleagues that in patients with pure CM with symmetrical C1/2 joints and no signs of instability, PFD and duraplasty is an established, effective, and safe treatment option with excellent long-term outcome [18,28,62,89]. In patients with instability, C1-2 fusion with distraction or OCF with or without transoral decompression in selected cases are potential treatment options that have to be considered in this patient population.…”
Section: Chiari Malformation Type I-discussion Of Evidencesupporting
confidence: 79%
“…The Only Treatment for Chiari Malformation Is Foramen Magnum Decompression With or Without Duroplasty: Behari et al [9] in his impressive review of literature has shown significant improvement (upto 70%) may be achieved both with foramen magnum with or without duroplasty [10]. He also stressed the low mortality of this procedure (<1%).…”
mentioning
confidence: 99%
“…The other top pick would be “Is Cervical Stabilization for All Cases of Chiari-I Malformation an Overkill? Evidence Speaks Louder Than Words!” presented by another master, Professor Sanjay Behari and Dr. Deora et al [3] The authors have answered for the 2 fundamental questions in a scientific way: (1) Has the FMD become outdated and has been replaced by posterior C1–2 stabilization in every case? and (2) In case posterior stabilization is required, should a C1–2 stabilization, rather than an occipitocervical fusion, be the only procedure recommended?…”
mentioning
confidence: 99%